PENGELOLAAN PENDIDIKAN KARAKTER DISIPLIN ANAK USIA DINI STUDI KASUS DI AL-MUNA ISLAMIC PRESCHOOL SEMARANG - A. Tabi'in (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2017)
Character education on early childhood nowadays is essential since Indonesian people are experiencing a crisis of character. Character here means one's manner, behavior, moral, or personality which is formed by internalization of virtue that they believed and used as the basic foundation of their perspective, ways of thinking, behaving and acting. This virtue includes moral values, and norms like being discipline, dare to act, and many others. Character building for children is designed to get them used to well-behaved which in turn will adopt it as their habit. This study aims to know how the discipline character education that has been run over the years, both in terms of planning, learning, assessment and supporting and inhibiting factors in early childhood discipline character education.This research applies qualitative approach with case study method. This research was conducted at Al-Muna Islamic Preschool Semarang. This research is aimed to find out the progress of discipline character education, either from its formulation, learning process, evaluation and supporting factors as well as inhibiting factors in implementing early childhood discipline character education. Method of data collection was carried out by interview, observation and documentation. includes the data reduction, the display data and the conclusion. The result of the research reveals that (1) the management of early childhood discipline character education was initiated with good learning formulation, the formulation of discipline character learning is well-integrated with existing learning by integrating discipline character education within the learning formulation. (2) The process of discipline character learning is carried out on daily basis and integrated with scheduled materials where each subject is adjusted with the topic. (3) The assessment method used in evaluating the discipline character education at Al-Muna Islamic Preschool employs anecdote notes, observation, and diaries. (4) The supporting and inhibiting factors in implementing discipline character education is teachers as role models for the students as well as the clear rules. The inhibiting factor is the implementation of child discipline character education that inconsistent.There are several recommendation to consider in this research, namely (1) the planning of child discipline character education should be developed in more systematic and detailed. (2) The child discipline character education should be consistent in each of the learning centers. (3) The assessment of child discipline character education need to be revisited and aligned with the assessment recommended by the National Ministry. (4) Teachers as the main model in giving the example of discipline, must show a direct/real examples of discipline at school to their students.